Seasonal and Spatial Variations in Demand for and Elasticities of Fish Products in the United States: An Analysis Based on Market‐Level Scanner Data. (25th February 2014) - Singh, Kehar; Dey, Madan M.; Surathkal, Prasanna
<x xml:space="preserve">Abstract</x> Seasonally and spatially varying demand elasticities would provide important information to seafood producers and marketers as well as policy makers. We analyzed the effects of season and space on (i) demand (translation effects) and (ii) price as well as expenditure elasticities of demand (scaling effects) for 13 finfish species in the United States. The paper used market‐level scanner data for 52 U.S. markets. Results suggest that not only the quantity demanded, but also the demand elasticities vary across species, seasons, and geography; not only does the degree of competition among finfish products vary considerably over space, but substituting products themselves change. These results highlight the importance of studying consumer demand behavior at species level, across seasons and geography, particularly as it sheds important light on some important policy issues such as the potential substitution between catfish and tilapia in the U.S. markets.